Toxicity assessment of nitric acid functionalized with iron oxide nanoparticles and sipeg as a new radiographic contrast media / Rasdin Ridwan - Ridwan, Rasdin (2015)
Engineered nanoparticles have been extensively explored in various biomedical settings including nanoparticulate imaging agents due to its promising benefits to mankind. Iodine-intolerance patients have caused alarming concerns in searching new contrast media with lower toxicity effect. However, proper potential mechanism of nanoparticles has yet to be fully established despite its early acceptance and emerging usage. By using animal model system, the aim of present study is to assess acute nanotoxicity of 14 nm iron oxide nanoparticles (IONPs) coated with nitric acid and silane-polyethylene glycol (SiPEG) in comparison to iodine. Eighteen male wistar rats were used in order to explore the underlying toxicity of IONPs in liver tissues. ·OH free radicals were elucidated by using reactive oxygen species (ROS) production assay and western blotting for the presence of p53 protein expression. The results revealed coated IONPs produced higher ROS level compared to iodine, however no statistical significant were observed. It can be hypothesized that higher amount of antioxidant has been produced by rats in iodine group in correlation to combat higher amount of ROS produced before assayed was conducted. Stronger expressions of p53 protein from the coated IONPs group were further observed. Expression of p53 protein suggested initiation of antioxidants production by the protein to ameliorate intracellular ROS production to further achieve normal redox balance in curtailing further damage. The outcomes highlighted that short-term administration of IONPs with different functionalization surfaces may be safe to be applied as radiographic contrast media.